‘I can do this’: a qualitative exploration of acceptability and experiences of a physical activity behaviour change intervention in people with multiple sclerosis in the UK - Cherry Kilbride; Meriel Norris; Jennifer M Ryan; Nana Anokye; Jennifer Fortune; Andrea Stennett; Grace Lavelle; Wendy Hendrie; Lorraine de Souza; Mohamed Abdul; Debbie Brewin; Lee David; et al. (BMJ Open)
Objectives The purpose of this study was to explore the experiences of people with multiple sclerosis (MS) who participated in iStep-MS, a feasibility randomised controlled trial of a behaviour change intervention that aimed to increase physical activity and reduce sedentary behaviour.Design A qualitative approach was undertaken embedded in the feasibility randomised controlled trial. One-to-one semi-structured interviews were conducted and analysed using Framework analysis.Setting Participants were recruited from a single MS therapy centre in the southeast of England, UK.Participants Sixty people with MS were randomly allocated in a 1:1 ratio to the intervention or usual care. Following a purposive sampling strategy, 15 participants from the intervention arm undertook 1:1 semi-structured interviews.Interventions The iStep-MS intervention consisted of four therapist-led sessions over 12 weeks, supported by a handbook and pedometer.Results Three themes were identified from the data. “I can do this”: developing competence in physical activity highlights the enhanced physical activity confidence gained through goal setting and accomplishment. “I felt valued”: the nurturing culture provides an overview of the supportive and non-judgemental environment created by the programme structure and therapeutic relationship. Finally, “What can I do?”: empowered enactment describes the transition from the supported iStep-MS intervention to intrinsically motivated physical activity enactment.Conclusions Overall, this study supports the acceptability of the iStep-MS intervention and identified key areas that supported participants to be physically active.Trial registration number ISRCTN15343862.